Prevalence and prognostic value of disseminated tumor cells in primary endometrial, cervical and vulvar cancer patients - Walter, Christina; Taran, Florin Andrei; Wallwiener, Markus; Rothmund, Ralf; Kraemer, Bernhard; Krawczyk, Natalia; Blassl, Christina; Melcher, Carola; Wallwiener, Diethelm; Fehm, Tanja; Hartkopf, Andreas Daniel (Future oncology, 2014)
: Aims: Disseminated tumor cell (DTC) detection in bone marrow (BM) of primary breast cancer patients predicts poor prognosis. This study investigates the prevalence of DTCs and their prognostic significance in primary gynecologic malignancies. Patients & methods: DTCs from BM aspirates of 603 patients with endometrial (311), cervical (228) and vulvar cancer (64) were identified by the pancytokeratin antibody A45B/B3. Results: DTCs were detected in 18% of BM aspirates (21, 16 and 16% in endometrial, cervical and vulvar cancer, respectively). In cervical cancer, DTCs were associated with International Federation of Gynecology and Obstetrics stage, nodal status and lymphangiosis. There was no association between BM status and prognosis. Conclusion: Tumor cell dissemination is common in gynecological cancer. In contrast to breast cancer, DTCs that derive from cervical, endometrial or vulvar cancer have less potential to initiate metastatic regrow. The molecular mechanisms underlying this observation warrant further investigation.